Mirodenafil for the Treatment of Erectile Dysfunction: A Systematic Review of the Literature - Park, Hyun Jun; Moon, Kyung Hyun; Lee, Seung Wook; Lee, Won Ki; Kam, Sung Chul; Lee, Jun Ho; Park, Nam Cheol (The world journal of men's health, 2014)
Phosphodiesterase type 5 (PDE5) inhibitors are the most commonly used treatment for erectile dysfunction (ED). Since the launch of sildenafil, several drugs-including mirodenafil, sildenafil citrate (sildenafil), tadalafil, vardenafil HCL (vardenafil), udenafil, and avanafil-have become available. Mirodenafil is a newly developed pyrrolopyrimidinone compound, which is a potent, reversible, and selective oral PDE5 inhibitor. Mirodenafil was launched in Korea in 2007, and an orally disintegrating film of mirodenafil was developed in 2011 for benefitting patients having difficulty in swallowing tablets. This study aimed to review the pharmacokinetic characteristic profile of mirodenafil and report evidence on its efficacy in the case of ED. In addition, we reviewed randomized controlled studies of mirodenafil's daily administration and efficacy for lower urinary tract symptoms.